Investigation of depth-area-duration (DAD) curves for Kuantan River Basin (KRB) - Norasman, Othman; Krishnan, B.; Syarifuddin, Misbari; Shairul Rohaziawati, Samat (IOP Publishing Ltd., 2024)
Depth-area-duration (DAD) analysis of rainfall is performed to evaluate the maximum amount of rainfall over areas of various sizes within different durations. It is frequently used to characterize precipitation extremes for the specification of so-called rainfall, with DAD curves resembling the correlation between rainfall depth and area. Kuantan River Basin (KRB) is one of the major rivers in Pahang that typically experiences heavy precipitation during the northeast monsoon season from November through March. In this study, DAD curves for KRB were developed for the duration of 1-day to 7-day. Daily rainfall data between 2008 to 2019 from eight stations in KRB were used to develop the DAD curves. DAD curve development initially requires an isohyet map's illustration that can be constructed through the interpolation of Inverse Distance Weighting (IDW) method. The isohyet maps were developed in the ArcGIS software to purposely obtain the average maximum rainfall depths for each rainfall duration. The maximum rainfall amount of 1-day up to 7-day durations increased from 394.45 mm to 857.61 mm. The results indicated that the maximum amount of rainfall will increase along with the duration from 1-day to 7-day. The gap between the final DAD curve of 6-day and 7-day was less compared to other duration curves; however, the gap for both curves increased from the 800 km2 to 1000 km2 areas where the gap differences between the curves accelerated from 12 mm to 34 mm. Final DAD curves of KRB were produced from the combination of initial DAD curves with durations ranging from 1 to 7 days. The DAD curves produced in this study can provide further information on the maximum rainfall depth under different storm durations for hydrological planning purposes, particularly in KRB.